THE EVOLUTION OF LITERARY CRITICISM DURING THE TWENTIETH CENTURY. - Mizrabova Jeren Ismailovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract:This study offers a systematic examination of the origins and historical development of women’s literary tradition alongside feminist criticism within European and American cultural and historical frameworks. It analyzes the principal phases in the evolution of feminist theoretical discourse in literary studies, beginning with early manifestations of women’s writing and the emergence of critical self- consciousness, and extending to the formal institutionalization of feminist discourse in the twentieth century.